2012
DOI: 10.5047/eps.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami-induced coastal change: scenario studies for Painan, West Sumatra, Indonesia

Abstract: There exists a high probability of a great earthquake rupture along the subduction megathrust under the Mentawai Islands of West Sumatra in the near future. Six rupture models were used to assess the tsunami inundation and the accompanying sediment movement in Painan, West Sumatra, Indonesia. According to a worst scenario, the potential tsunami might hit the coast of Painan about 26 minutes after the rupture and the entire city could be inundated with a maximum inundation depth of about 7 m. Severe erosion may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…These parameters were applied following previous studies [20,26]. C eq represents the equilibrium sediment concentration calculated according to [21] as the following approximation:…”
Section: ∂Hc ∂Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters were applied following previous studies [20,26]. C eq represents the equilibrium sediment concentration calculated according to [21] as the following approximation:…”
Section: ∂Hc ∂Tmentioning
confidence: 99%
“…The studies revealed that the COMCOT-SED model results were consistent with measurements of tsunami deposit data. This model has also been used to investigate the impact of morphological change from a future tsunami in Painan, West Sumatra, Indonesia [21].…”
Section: Introductionmentioning
confidence: 99%
“…Coastal topography may constantly change with numerous oceanic and physical processes including tidal flooding, SLR, and tsunami effect. This may cause sinking of low-land areas, and erosion of sediments which is a great concern for coastal researchers and investigators [10][11][12][13][14]. Further sediments excavation, river modification and construction along coastal areas also play an important role in coastal areas including the BIs [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of demographic, geomorphological, geological, and shoreline change data obtained from remote sensing accommodates a representative resilience assessment in Seribu Islands, Jakarta [20]. In addition, shoreline data, obtained using remote sensing technology, can be used as an input for modeling tsunami inundation [21] and identifying the impacts of climate change and sea level rise-induced environmental change [22].…”
Section: Introductionmentioning
confidence: 99%